Arsenic trioxide and all-trans retinoic acid suppress the expression of FLT3-ITD. Issue 11 (18th September 2020) - Liang, Cong; Peng, Chun-Jin; Wang, Li-Na; Li, Yu; Zheng, Li-Min; Fan, Zhong; Huang, Dan-Ping; Tang, Wen-Yan; Zhang, Xiao-Li; Huang, Li-Bin; Tang, Yan-Lai; Luo, Xue-Qun
Abstract: The prognosis of patients with acute myeloid leukemia (AML) caused by the FLT3-ITD mutation is poor. Arsenic trioxide (ATO) and all-trans retinoic acid (ATRA) can down-regulate FLT3-ITD level and selectively kill leukemia cells carrying the FLT3-ITD mutation. However, the mechanisms of action of these two compounds are unknown. Here, we found that ATO could bind FLT3-ITD at Lys91 and Asp225, whereas ATRA could bind FLT3-ITD at Lys5 and Gln6. Both compounds could not bind wild-type FLT3. Further studies revealed that ATO/ATRA may suppress the Expression of FLT3-ITD by promoting the UBE2L6-mediated ubiquitination pathway and decreasing the expression of C-MYC. However, further studies are needed to define the mechanisms of these compounds on AML. Our research provides an experimental basis for the use of ATO/ATRA in FLT3-ITD AML in clinical practice.